Duration of treatment in pulmonary tuberculosis: are international guidelines on the management of tuberculosis missing something?. Issue 6 (June 2015) - Atif, M.; Sulaiman, S.A.S.; Shafie, A.A.; Babar, Z.U.
Abstract Background Despite evidence of an association between tuberculosis (TB) treatment outcomes and the performance of national tuberculosis programmes (NTP), no study to date has rigorously documented the duration of treatment among TB patients. As such, this study was conducted to report the durations of the intensive and continuation phases of TB treatment and their predictors among new smear-positive pulmonary tuberculosis (PTB) patients in Malaysia. Study design Descriptive, non-experimental, follow-up cohort study. Methods This study was conducted at the Chest Clinic of Penang General Hospital between March 2010 and February 2011. The medical records and TB notification forms of all new smear-positive PTB patients, diagnosed during the study period, were reviewed to obtain sociodemographic and clinical data. Based on standard guidelines, the normal benchmarks for the durations of the intensive and continuation phases of PTB treatment were taken as two and four months, respectively. A patient in whom the clinicians decided to extend the intensive phase of treatment by ≥2 weeks was categorized as a case with a prolonged intensive phase. The same criterion applied for the continuation phase. Multiple logistic regression analysis was performed to find independent factors associated with the duration of TB treatment. Data were analyzed using Predictive Analysis Software Version 19.0. Results Of the 336 patients included in this study, 261 completed the intensive phase of treatment, and 226 completed the continuation phase of treatment. The mean duration of TB treatment (n = 226) was 8.19 (standard deviation 1.65) months. Half (49.4%, 129/261) of the patients completed the intensive phase of treatment in two months, whereas only 37.6% (85/226) of the patients completed the continuation phase of treatment in four months. On multiple logistic regression analysis, being a smoker, being underweight and having a history of cough for ≥4 weeks at TB diagnosis were found to be predictive of a prolonged intensive phase of treatment. Diabetes mellitus and the presence of lung cavities at the start of treatment were the only predictors found for a prolonged continuation phase of treatment. Conclusions The average durations of the intensive and continuation phases of treatment among PTB patients were longer than the targets recommended by the World Health Organization. As there are no internationally agreed criteria, it was not possible to judge how well the Malaysian NTP performed in terms of managing treatment duration among PTB patients.